Assessment of Electrocardiographic Changes and Associated Factors Among Thyroid Dysfunction Patients Attending Jimma Medical Center, Southwest Ethiopia: A Cross-Sectional Study - Zeleke M; Badanie A; Asefa ET; Reta Demissie W; Chala G; Aman H; Feyisa TO; Habte ML (International Journal of General Medicine, 2023)
Mastewal Zeleke,1 Almaz Badanie,2 Elsah Tegene Asefa,3 Wondu Reta Demissie,2 Getahun Chala,1 Husen Aman,4 Teka Obsa Feyisa,5 Mezgebu Legesse Habte5 1Department of Medical Physiology, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2Department of Biomedical Sciences, College of Medicine and Health Sciences, Jimma University, Jimma, Ethiopia; 3Department of Medicine, College of Medicine and Health Sciences, Jimma University, Jimma, Ethiopia; 4Department of Human Anatomy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 5Department of Medical Biochemistry, College of Health and Medical Sciences, Haramaya University, Harar, EthiopiaCorrespondence: Mastewal Zeleke, Department of Medical Physiology, College of Health and Medical Sciences, Haramaya University, P.O.Box:235, Harar, Harari Regional State, Ethiopia, Tel +251911142917, Email mastewalzeleke2015@gmail.comBackground: Thyroid dysfunction (TD) is a metabolic manifestation related to either excessive or inadequate production of thyroid hormones. It has been widely proven to have comorbidities like cardiovascular disease. An electrocardiograph is a simple investigative instrument used to assess cardiac status to prevent complications in the later stages of the disease.Objective: To assess electrocardiogram (ECG) changes and associated factors among TD patients.Methods: An institution-based cross-sectional study was conducted among 273 TD patients attending Jimma Medical Center from October 11 to December 11, 2021. An ECG tool with 12 leads was used to assess the cardiac status, and a semi-structured questionnaire was used to assess sociodemographic, behavioral, and comorbidity variables. Bodyweight, height, waist circumference (WC), hip circumference (HC), and blood pressure variables were recorded, and body mass index (BMI) and waist-to-hip ratio (WHR) were calculated.Results: Out of a total of 273 analyzed and interpreted ECG results by the cardiologists, 185 (67.8%) had ECG alterations. The most common types of ECG changes were arrhythmia 153 (56%), followed by myocardial infarction 74 (27.1%), ventricular hypertrophy [left 20 (7.3%) and right 15 (5.5%)], left atrial enlargement 3 (1%), axis deviation, and other abnormalities 24 (8.8%) and 18 (6.6%), respectively. The identified predictor variables for the ECG changes were the age group of 41 to 60 years old [AOR = 2.5, 95% CI: 1.25, 5.05], being female [AOR = 2.7, 95% CI: 1.28, 5.59], having diabetes mellitus [AOR = 4.25, 95% CI: 1.6, 11.2], and not starting the treatment [AOR = 8.6, 95% CI: 3.45, 21.6].Conclusion: This study revealed that the prevalence of ECG changes was high among TD patients. The most common type of ECG change observed was arrhythmia followed by myocardial infarction. The age range of 41– 60 years old, being female, having diabetes mellitus, and not starting the treatment were significantly associated with the ECG changes. Implementing an efficient noninvasive screening of cardiac status can detect unrecognized and asymptomatic cardiac impairment in TD patients.Keywords: cardiovascular disease, electrocardiogram, Ethiopia, thyroid dysfunction